Problem Gambling in Europe Challenges, Prevention, and Interventions - Meyer, Gerhard; Hayer, Tobias; Griffiths, Mark (Springer New York : Imprint: Springer, 2009)
Problem Gambling in Europe Challenges, Prevention, and Interventions Edited by Gerhard Meyer, University of Bremen, Germany Tobias Hayer, University of Bremen, Germany Mark Griffiths, Nottingham Trent University, United Kingdom As a leisure activity, gambling dates back to ancient times. More recently, the surge in avenues for gambling-casinos, sports betting, lotteries, and remote media (e.g.,Internet, mobile phone, interactive television) among them-finds growing numbers of people losing control over their gambling behaviour, usually at great personal and financial expense. Problem Gambling in Europe is the first book to offer a robust international knowledge base compiled by an interdisciplinary panel of researchers in gambling behaviour. Reports from 21 countries throughout Western, Eastern, Northern, and Southern Europe reveal wide variations in types of wagering activities, participation by populations, social and criminal consequences related to pathological gambling, the extent to which governments acknowledge the problem, and efforts to control it (often with the involvement of the gaming industries). For each country, noted experts discuss: Current legislation regulating gambling. Forms of gambling and their addictive potential. Participation rates and demographics. Prevalence of pathological gambling. National policies to address problem gambling. Prevention strategies and treatment methods. Problem Gambling in Europe brings insight and clarity to a widespread and complex phenomenon, and will be of considerable interest to all parties working to reduce their negative effects: social science researchers in addictions, gambling behaviour, and public health; clinical, social, and health psychologists and psychiatrists; treatment practitioners; the gaming industry; regulators; and policy makers.